Ice Flow in the North East Greenland Ice Stream - Joughin, I.; Fahnestock, M.; Bamber, J.; MacAyeal, D. (2004)
We have measured ice flow and detailed topography in northeastern Greenland using satellite-based Synthetic Aperture Radar (SAR) interferometry.